Motivating state's moral duties to foreign domestic workers through care ethics - Escanuela Allysa Vea Giner (Nanyang Technological University, 2024)
Increasing female labour force participation, the nature of modern work, and an ageing population have posed significant challenges to meeting the caregiving needs of families in Singapore. Overall, these challenges have resulted in a ‘care drain’. This phenomenon has prompted households and the state to rely on foreign domestic workers (FDWs) to fill the gap. Despite this dependence, FDWs are, owing to the policies and systems that govern their employment, subject to much exploitation and abuse. Human rights approaches inspired by justice-oriented theories like Martha Nussbaum’s capabilities approach have been used to argue for state duties towards FDWs. These approaches, however, often fall short due to problems arising from its metaphysical ontology of human nature and the consent that underlies FDWs’ employment arrangements in Singapore. In contrast, care ethics offers a more compelling framework for valuing and improving the well-being of FDWs. Care ethics, with its relational ontology, provides a stronger justificatory basis for state duties to care, and is able to generate moral duties that extend to all members of society. Overall, this paper aims to explore the inadequacies of current approaches in motivating state action and argues for the potentiality of care ethics in better justifying state responsibilities towards FDWs.